2019
DOI: 10.1007/s10433-019-00501-5
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of home and health dynamics among younger older people in Sweden

Abstract: Research has shown that positive evaluations of home are important for very old people’s health, well-being and independence in daily life. The rationale for the present study derives from our survey study findings, confirming such associations also in a younger cohort ( N = 371). The purpose of this study was to further increase the understanding of the dynamics of meaning of home and health among community-living healthy younger older people, in the present and in a projected future. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
(65 reference statements)
1
21
0
Order By: Relevance
“…Living at home is meaningful as it promotes the experience of having control over one's life (Oswald et al, 2006). Especially when people are less able to function, home provides roots for personal identity as well as supporting experiences of security and freedom (Dahlin-Ivanoff et al, 2007;Kylén et al, 2019). For ageing individuals, losing autonomy and being forced to follow the rules of others causes suffering (Reis et al, 2019(Reis et al, : 1634(Reis et al, -1635.…”
Section: Significance Of Autonomymentioning
confidence: 99%
“…Living at home is meaningful as it promotes the experience of having control over one's life (Oswald et al, 2006). Especially when people are less able to function, home provides roots for personal identity as well as supporting experiences of security and freedom (Dahlin-Ivanoff et al, 2007;Kylén et al, 2019). For ageing individuals, losing autonomy and being forced to follow the rules of others causes suffering (Reis et al, 2019(Reis et al, : 1634(Reis et al, -1635.…”
Section: Significance Of Autonomymentioning
confidence: 99%
“…In a qualitative study with people over 65 years in Sweden, the results indicated that one's home became increasingly important after retirement, and that living in a community dwelling had emotional and social benefits for the dwellers. 14 In other words, one's living situation is very important in helping them develop resources to deal with problems effectively, adapt to changes, lead meaningful lives and protect their self-integrity. Thus, determining the elderly's mental health symptoms, meaning in life and spiritual well-being according to the place of living is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Building on that, Wahl and Oswald [13] stated that older people perceiving more meaning in relation to the housing could become "prisoners of space" in a no-longer-fitting housing environment. Relocation in very old age has been further described as a complex and ambivalent process [51], which is also true for younger older people [20]. Such dynamics might explain some of the somewhat mixed results of the present study, not the least in particularly challenged groups, such as people ageing with PD.…”
Section: Plos Onementioning
confidence: 50%
“…Moreover, research using the MOH suggests that meaning of home rating patterns may change over time [12] and should therefore not be considered as temporally consistent. For instance, based on qualitative in-depth interviews Kylén and colleagues [20] pointed out that thoughts on future housing in later life, including issues of meaning of home exists already at the time of retirement.…”
Section: Perceived Aspects Of Housingmentioning
confidence: 99%